Rereading Normal Science - Dimitri Ginev (Crítica)
This paper considers the relevance of a class of hermeneutic concepts to the philosophical reading of normal scientific research. The author opposes the view that the notion of "normal science" can only be read in socio-psychological, sociological or ethnomethodological terms. By drawing parallels between Kuhn's original reading of puzzle-solving enterprise and Gadamer's philosophical hermeneutics, a context of "Continental theories" for interpreting the dynamics of research practices is delineated. The rereading of normal science provides the opportunity for developing a hermeneutic alternative to the analytic philosophy of science.